Analysis of Paintings by Children with Autism as an (Art Therapy Effort) - Seniman, Anugrah Fadly Kreato; Sukinah, Sukinah (IJOSMAS, 2025)
This study aims to obtain the characteristics of the appropriate creative process in art therapy. Through this descriptive analysis, the characteristics of the appropriate work created through the art therapy process will be discovered. The main focus of the study is to analyze the paintings of autistic individuals studied through the art therapy process. This study used a descriptive qualitative research method, namely analyzing the works of 9 autistic children in Yogyakarta, Bandung, and Jakarta. The main focus of the study was to collect qualitative data through interviews, questionnaires, and observations covering the process of representation of the work, namely: (1) the process of objectification, (2) the process of symbolization, and (3) the process of expression. The technique of analyzing the painting is related to the use of symbols and ways of expressing. The results of the study show that the process of creating the work is carried out through an unexpected process, achieving visual surprise (aha erlebnis), honesty in expressing inner thoughts (silent expression), incidental and spontaneous expression (spontaneous expression). However, in some of the individual works studied, visual achievements were found that did not reflect honesty and spontaneity (spontaneous expression). This is likely due to the role of teacher and parent intervention that directed towards a good final result so that it did not reflect the honesty of the child's work